How Does Employee Discipline Enhance Service Quality at Assistant Health Center? - Andrian, Debi; Ikbal, Muhammad; Useng, Abd. Razak (Jurnal Studi Ilmu Pemerintahan, 2024)
This study examines the effect of employee work discipline on service quality at the Auxiliary Public Health Center in Kalempang Village, Sidenreng Rappang Regency. The research employed a quantitative descriptive method using questionnaires as the primary data collection instrument, with 60 respondents participating. The data were analyzed using statistical tools, including simple linear regression and hypothesis testing, with a significance level of 5 percent. The results show a significant percent positive correlation of 70 percent between employee discipline and service quality. The regression analysis further supports that 77 percent of the variability in service quality can be attributed to work discipline, with a t-value of 3.623 exceeding the t-table value of 1.672. This suggests that better work discipline improves service quality, particularly regarding employee punctuality, reliability, and responsiveness. However, the research also identifies several challenges, including the incomplete infrastructure at the health center, which affects the overall service quality. The implications of this study highlight the need for improved staff discipline and infrastructure development to enhance public service satisfaction in rural health facilities. The study contributes to the existing body of knowledge by providing empirical evidence on the importance of work discipline in improving service quality in the health sector. Limitations include the focus on a single health facility, which limits the generalizability of the findings. Future studies should consider expanding the scope of the research to include multiple health facilities and regions for a broader understanding.